A novel anticancer pharmacological agent targeting mitochondrial complex I. (September 2022) - Reyes-Castellanos, Gabriela; Carrier, Alice
Abstract : Targeting metabolic reprogramming has proven successful in oncology, but this field requires better identification of drugs that inhibit mitochondrial metabolism in cancer cells. Recent work from Dr Wolf's group reveals that the primary target of the antitumor compound SMIP004-7 is mitochondrial complex I (NDUFS2 subunit), inhibition of which promotes anticancer immune surveillance.